(untitled) (Annals of Library and Information Studies, 2025)
This study explores the development of Open Access (OA) publications in the Indian Knowledge System (IKS) between 2005 and 2024, highlighting trends in access models, citation impact, licensing, and research themes. The data from OpenAlex, 9,326 records, were analyzed to assess the growing role of OA in disseminating India’s traditional knowledge, encompassing disciplines such as Ayurveda, Yoga, Indigenous sciences, and Indian philosophy. Findings indicate that over the past 20 years, there has been a notable shift towards OA publishing, with Gold and Bronze OA becoming the most popular and frequently cited models. While licensed OA content, primarily under Creative Commons, has increased—especially CC-BY-NC—many Bronze OA articles remain without clear licensing, raising issues of reuse and legal clarity. Compared to closed access, authorship patterns in OA works demonstrate greater collaboration. Thematic analysis reveals a dynamic convergence of traditional knowledge with modern fields such as satellite imaging, AI in agriculture, and alternative medicine. Productive journals and publishers demonstrate varied OA strategies, influencing impact and visibility. Thus, the OA has been essential in increasing the visibility of IKS research worldwide. However, standardisation, licensing clarity, and inclusive access continue to be issued, necessitating deliberate efforts to promote sustainable OA practices in this vital field.